Android-Based Educational Game Learning Media Containing Gending Rare Local Wisdom on Science Subjects for Grade 5 Elementary Schools - Ni Made Milayani Suarningsih; I Gede Margunayasa; I Wayan Lasmawan (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2024)
Android-based educational game media based on local wisdom, Gending Rare, is a solution to the problem of low student learning outcomes. This research aims to produce Android-based educational game learning media containing local wisdom of gending rare in science subjects for grade 5 elementary school. This research is development research using the ADDIE model. This model is divided into five steps, namely: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The research results are; (1) Android-Based Educational Game Learning Media Containing Gending Rare Local Wisdom in Science Subjects for Grade 5 Elementary School in the form of an application that can be installed on a smartphone. (2) The validity test obtained the qualification "Very Valid and Suitable for use. (3) The practicality test obtained the qualification "Very Practical and Interesting”. (4) Based on the calculation of the pretest and posttest results with the correlated sample t-test, it is known that the average pretest value is 59.68 and posttest is 81.60 with a sig value. (2-tailed) less than 0.05. So, the Android-based educational game learning media containing local wisdom of gending rare in science subjects for grade 5 elementary school is valid, practical and effective in improving students' science learning outcomes. This research has implications for education as a solution media in responding to low student learning outcomes.